2016
DOI: 10.1371/journal.pone.0145615
|View full text |Cite
|
Sign up to set email alerts
|

Novel Promising Estrogenic Receptor Modulators: Cytotoxic and Estrogenic Activity of Benzanilides and Dithiobenzanilides

Abstract: The cytotoxicity of 27 benzanilides and dithiobenzanilides built on a stilbene scaffold and possessing various functional groups in aromatic rings previously described for their spasmolytic properties was assayed on three human cancer cell lines (A549 –lung adenocarcinoma, MCF-7 estrogen dependent breast adenocarcinoma and MDA-MB-231 estrogen independent breast adenocarcinoma) and 2 non-tumorigenic cell lines (CCD39Lu–lung fibroblasts, MCF-12A - breast epithelial). Three compounds (6, 15 and 18) showed selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Docking serves either to investigate the binding of estradiol to the ER or to dock other molecules, potentially new drugs, such as potent and highly selective estriol analogues [ 69 ]. In the second case, information from previous studies on estradiol behavior in an active site serves as reference data [ 70 , 71 , 72 , 73 ]. This is a starting point for the commonly applied research sequence: investigation of E2 binding mode, comparison with the calculation results for potential drugs, and confirmation of the hypothesis by analytical techniques.…”
Section: Application Of Molecular Modelling Methods In the Study Omentioning
confidence: 99%
See 1 more Smart Citation
“…Docking serves either to investigate the binding of estradiol to the ER or to dock other molecules, potentially new drugs, such as potent and highly selective estriol analogues [ 69 ]. In the second case, information from previous studies on estradiol behavior in an active site serves as reference data [ 70 , 71 , 72 , 73 ]. This is a starting point for the commonly applied research sequence: investigation of E2 binding mode, comparison with the calculation results for potential drugs, and confirmation of the hypothesis by analytical techniques.…”
Section: Application Of Molecular Modelling Methods In the Study Omentioning
confidence: 99%
“…This is a starting point for the commonly applied research sequence: investigation of E2 binding mode, comparison with the calculation results for potential drugs, and confirmation of the hypothesis by analytical techniques. Such a three-step process has been performed, for example, for estrogen-dependent MCF-7 cancer cells [ 70 ]. Eighteen compounds with antiproliferative activity have been docked into the cavity where E2 normally binds.…”
Section: Application Of Molecular Modelling Methods In the Study Omentioning
confidence: 99%
“…For example, 2-hydroxy-N-(4-hydroxyphenyl) benzamide, also known as osalmid (Figure 9) is a medicine used for treating acute and chronic cholecystitis and gallstone disease [178]. Previously, the literature data reported that osalmid is a potential ribonucleotide reductase small subunit M2-targeting compound with potent activity against a lamivudine (3TC)-resistant hepatitis B virus strain in vitro and in vivo [191].…”
Section: Significant Progress Of Benzanilides-small Group With Large mentioning
confidence: 99%
“…The anticancer effect was confirmed in the OCI-LY8 xenograft model. Administration of DCZ0858 significantly prevented tumour growth by decreasing cell proliferation and inducing apoptosis without causing any damage to important organs [178]. Currently, osalmid is under clinical trial in the treatment of MM (ClinicalTrials.gov).…”
Section: Significant Progress Of Benzanilides-small Group With Large mentioning
confidence: 99%
See 1 more Smart Citation